Effects of short‐term sex steroid suppression on dietary fat storage patterns in healthy males. Issue 2 (22nd January 2018) - Rynders, Corey A.; Schmidt, Stacy L.; Bergouignan, Audrey; Horton, Tracy J.; Bessesen, Daniel H.
Abstract: Hypogonadism in males is associated with increased body fat and altered postprandial metabolism, but mechanisms remain poorly understood. Using a cross‐over study design, we investigated the effects of short‐term sex hormone suppression with or without testosterone add‐back on postprandial metabolism and the fate of dietary fat. Eleven healthy males (age: 29 ± 4.5 year; BMI: 26.3 ± 2.1 kg/m 2 ) completed two 7‐day study phases during which hormone levels were altered pharmacologically to produce a low sex hormone condition (gonadotropin releasing hormone antagonist, aromatase inhibitor, and placebo gel) or a testosterone add‐back condition (testosterone gel). Following 7 days of therapy, subjects were administered an inpatient test meal containing 50 μCi of [1‐ 14 C] oleic acid. Plasma samples were collected hourly for 5 h to assess postprandial responses. Energy metabolism (indirect calorimetry) and dietary fat oxidation ( 14 CO2 in breath) were assessed at 1, 3, 5, 13.5, and 24 h following the test meal. Abdominal and femoral adipose biopsies were taken 24 h after the test meal to determine uptake of the labeled lipid. Postprandial glucose, insulin, free‐fatty acid, and triglyceride responses were not different between conditions ( P  > 0.05). Whole‐body energy metabolism was also not different between conditions at any time point ( P  > 0.05). Dietary fat oxidation trended lower ( P  = 0.12) and the relative uptake of 14 C labeled lipid into femoral adipose tissue was greater ( P  = 0.03) in the low hormone condition. Short‐term hormone suppression did not affect energy expenditure or postprandial metabolism, but contributed to greater relative storage of dietary fat in the femoral depot. ClinicalTrials.gov Identifier: NCT03289559. Abstract : Hypogonadism in males is associated with increased adiposity and altered dietary fat metabolism, but the specific role of low testosterone in these age‐related changes is not well understood. Using a pharmacological model of gonadal aging in young men (GnRH antagonist ± testosterone), we found that low testosterone was not associated with altered energy expenditure, fuel utilization, or postprandial metabolism. However, low testosterone did contribute to greater storage of dietary fat in the femoral depot.